The problem of inequality in Australia's early childhood education and care sector: A policy frame analysis. Issue 3 (November 2019) - Molla, Tebeje; Nolan, Andrea
A policy problem is a discursive construction, and the way in which the problem is framed determines both the nature of the policy responses and the possibility of resolving it. In this paper, drawing on critical frame analysis, we examined three major equity policies in the Australian early childhood education and care (ECEC) sector. In mapping out framing and reasoning devices of the policies, our analytical interest is to highlight the representation of inequality as a problem and unmask underlying assumptions of the equity responses. The findings show that disadvantage in Australia's ECEC sector has been framed as a lack of access, limited navigational capacity and cultural exclusion; and the framings are underpinned by economic, educational and social rationales. The analysis also reveals problematic categories, issue-omissions and conceptual shifts within the texts. The paper draws practical implications of the frame contradictions and silences.